1986
DOI: 10.1002/eji.1830160506
|View full text |Cite
|
Sign up to set email alerts
|

Ir gene expression on T cells: Effect of a monoclonal antibody directed against I region‐controlled determinants on T cells

Abstract: A monoclonal antibody directed at an I region-controlled epitope uniquely expressed on T cells (Iat) was studied for its in vivo effect on the antibody response under the control of an Ir gene. The antibody was produced by a hybridoma made from A.TH spleen cells immune to A.TL (anti-Ik), that was selected for its reactivity with T but not B cells and macrophages, and thus was designated as anti-IatK. The injection of this anti-Iatk into H-2k, H-2b and H-2k X bF1 mice resulted in the suppression of antibody res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1988
1988

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Anti-Iat have been shown to inhibit autologous and allogeneic mixed lymphocyte reaction by blocking the responder T cells but not stimulators (26) . The in vivo administration of an anti-Iatk was found (12) to be inhibitory for the H-2k-restricted helper T cell activity . We have recently observed that anti-Iatk are able to induce polyclonal proliferative response of a fraction of normal unprimed T cells of H-2k mice (Yagi, J ., Y. Asano, and T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-Iat have been shown to inhibit autologous and allogeneic mixed lymphocyte reaction by blocking the responder T cells but not stimulators (26) . The in vivo administration of an anti-Iatk was found (12) to be inhibitory for the H-2k-restricted helper T cell activity . We have recently observed that anti-Iatk are able to induce polyclonal proliferative response of a fraction of normal unprimed T cells of H-2k mice (Yagi, J ., Y. Asano, and T .…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies reactive with I region-controlled pol morphic determinants of H-2k haplotype that are uniquely expressed on T cells (anti-Iat ; 1 L9, 2L2, and 74L) are those described in previous papers (10)(11)(12) . 2 These anti-Iatk are the products of hybridomas derived from spleen cells of A .TH immune to A .TL lymphoid cells, and have been selected in the criteria that they can react with an augmenting T cell hybridoma (20) and some functional T cells but not with B cells and macrophages of H-2 k strains.…”
Section: Antibodiesmentioning
confidence: 99%
“…I-j is in many respects analogous to Iat, as it is expressed only on functional T cells (5). Although IJ was first demonstrated on Ts and TsF (1,2), it has been detected on a variety of T cell subsets including Th, Ts-inducer, and MLR responders (15,(28)(29)(30)(31) . It has recently been demonstrated that IJ can be adaptively expressed by T cells of different genotype that have developed in the radiation bone marrow chimera and in transgenic mice (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%